Conceptual Metaphors of Sexual Activities in Indonesian - I Dewa Putu Wijana; I Desak Ketut Titis Ary Laksanti (Balai Bahasa Sulawesi Selatan, 2024)
This article intends to investigate and applying conceptual metaphor theory proposed by Lakoff and Johnson concerning sexual activities in Indonesian. All data presented in this paper are mostly collected from You Tube pornographic cinema narration comments. First all metaphorical expressions in the data collection are carefully observed. Further they are classified based on themes, and only ones related to sexual matters are chosen and brought into consideration, and the others are neglected. Through close examination toward those sexual metaphorical expressions, it is found that there are various possibilities of Indonesian speakers conceptually to perceive the sexual activities. The sexual activities can be conceived as “war and fighting”, “gardening and farming”, “food enjoying”, “paddling”, “Seal Breaking and Goal Piercing”, “Shell Cracking”, etc. These perception possibilities are inseparable from sociocultural factors and realities that exist within Indonesian speech community.